2001
DOI: 10.1146/annurev.arplant.52.1.67
|View full text |Cite
|
Sign up to set email alerts
|

HOWGIBBERELLINREGULATESPLANTGROWTH ANDDEVELOPMENT: A Molecular Genetic Analysis of Gibberellin Signaling

Abstract: Gibberellins are hormones that control growth and a wide variety of other plant developmental processes. In recent years, significant progress has been made on the biochemistry of gibberellin biosynthesis and on the mechanisms by which gibberellin levels are regulated in plants. There have also been major advances in the understanding of gibberellin signaling, with several key genes being cloned. This review discusses our current understanding of gibberellin signaling, as seen from the perspective of molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
336
1
17

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 478 publications
(372 citation statements)
references
References 103 publications
4
336
1
17
Order By: Relevance
“…Gibberellin induces seed germination and promotes hypocotyl and stem elongation (PENG; HARBERD, 2000;RICHARDS et al, 2001). The use of growth regulators…”
Section: Introductionmentioning
confidence: 99%
“…Gibberellin induces seed germination and promotes hypocotyl and stem elongation (PENG; HARBERD, 2000;RICHARDS et al, 2001). The use of growth regulators…”
Section: Introductionmentioning
confidence: 99%
“…Specific roles of GA include the induction of seed germination, promotion of hypocotyls, stem elongation, regulation of pollen development and flower initiation, and wood formation (Mauriat and Moritz 2009;Richards et al 2001;Ritchie and Gilroy 1998). Many previous studies have shown that exogenous GA reduces the minimum effective exposure time to the germination stimulant and promotes seed germination (Chae et al 2004;Song et al 2005a, b).…”
Section: Introductionmentioning
confidence: 99%
“…A giberelina, importante regulador endógeno de crescimento, produz diversos efeitos sobre o crescimento e desenvolvimento, destacando-se indução da germinação em sementes, promoção do alongamento do hipocótilo e caule e regulação do desenvolvimento do pólen e indução floral (Peng e Harberd, 2000;Richards et al, 2001). Respostas variadas à aplicação de ácido giberélico (GA 3 ) na germinação de sementes foram verificadas por Perez-Garcia e Durán (1990) em Onopordum nervosum Boiss.…”
Section: Introductionunclassified